Ratio Decidendi Penolakan Permohonan Pengujian Norma Undang-Undang pada Putusan Nomor 47/PUU-XXI/2023 - Saputri, Tiara Ika; Pratama, Agung Barok (Manabia: Journal of Constitutional Law, 2024)
This research aims to explore the ratio decidendi in the Constitutional Court Decision Number 47/PUU-XXI/2023 and analyze the application of constitutional values contained in the decision. This research uses a normative method with statutory, conceptual, and case approaches. This approach aims to understand the legal basis on which the Constitutional Court's decision is based and its implications for the protection of constitutional rights. The results showed that the Constitutional Court rejected the petition for norm testing in Article 509 letter a of the latest Criminal Code. The rejection was based on the provision that the new Criminal Code will be enacted after three years since its enactment, so the petition was considered premature. In its decision, the Court emphasized the importance of the principle of legal certainty and the protection of advocates' rights from unconstitutional criminal threats. However, the petition could not be accepted due to the lack of concrete harm experienced by the petitioner. This finding underscores that the Constitutional Court continues to prioritize basic constitutional principles in its decision-making, even though the petition did not proceed to material examination. Thus, this research makes an important contribution in understanding how constitutional values are applied in the Constitutional Court's decisions, particularly in relation to the review of criminal law norms. The implications of this research are expected to be a reference in the development of the study of constitutional law and the protection of human rights in Indonesia.